Thin film optoelectronic devices using delafossite typr metal oxides and methods of their fabrication - (:unkn) unknown (My University, 2015)
A novel method for fabricating delafossite type metal oxides thin films, and the novel electrically active delafossite type metal oxides thin film are presented. The method comprises: providing a liquid-phase film material comprising a solution of a precursor material having at least one metal ion source and at least one selected fuel compound in at least one selected polar solvent; and using the liquid-phase film material for fabricating a multi-layer structure comprising at least one optically active layer configured with desired optical, electronic and mechanical properties. The film material is deposited on a surface of a structure comprising the optically active layer, and a post deposition treatment is applied to the deposited film material to transform the film material into an electrically active delafossite type metal oxide film being a semi- crystalline film comprising amorphous and crystalline regions.
Keywords: Film optoelectronic; international: H01L21/368; cooperative: H01L21/02565; Metal oxydes; cooperative: H01L21/02628; cooperative: H01L21/02581; cooperative: H01L21/02579